Screen time behaviours may interact with obesity genes, independent of physical activity, to influence adolescent BMI in an ethnically diverse cohort. Issue 6 (30th August 2013) - Graff, M.; North, K. E.; Richardson, A. S.; Young, K. M.; Mohlke, K. L.; Lange, L. A.; Lange, E. M.; Harris, K. M.; Gordon‐Larsen, P.
Summary Background There has been little investigation of gene‐by‐environment interactions related to sedentary behaviour, a risk factor for obesity defined as leisure screen time (ST; i.e. television, video and computer games). Objective To test the hypothesis that limiting ST use attenuates the genetic predisposition to increased body mass index (BMI), independent of physical activity. Design Using 7642 wave II participants of the National Longitudinal Study of Adolescent Health, (Add Health; mean = 16.4 years, 52.6% female), we assessed the interaction of ST (h week−1) and 41 established obesity single nucleotide polymorphisms (SNPs) with age‐ and sex‐specific BMI Z‐scores in 4788 European–American (EA), 1612 African–American (AA) and 1242 Hispanic American (HA) adolescents. Results Nominally significant SNP*ST interaction were found for FLJ35779 in EA, GNPDA2 in AA and none in HA (EA: beta [SE] = 0.016[0.007]), AA: beta [SE] = 0.016[0.011]) per 7 h week−1 ST and one risk allele in relation to BMI Z‐score. Conclusions While for two established BMI loci, we find evidence that high levels of ST exacerbate the influence of obesity susceptibility variants on body mass; overall, we do not find strong evidence for interactions between the majority of established obesity loci. However, future studies with larger sample sizes, or that may build on our current study and the growing published literature, are clearly warranted.